Effleurage Massage: Alternative Non-Pharmacological Therapy in Decreasing Dysmenorrhea Pain - Naning Puji Suryantini; Asirotul Ma rifah (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2022)
Background: Dysmenorrhea is the most general gynecological problem experienced by women of various ages level. Dysmenorrhea is a pain in the lower abdomen, it felt centered in the suprapubic area and can spread to the lower back and the back of the legs. The actions that can be taken to manage menstrual pain include abdominal heat therapy, abdominal massage, exercise, rest and sleep, relaxation techniques and natural diuresis. Effleurage massage is a technique with calm rhythmic, gentle pressure distally or downwards. In this research, massage was carried out for 3 minutes. Dysmenorrhea prevalence in Indonesia is very high at 64.25%. Dysmenorrhea interferes with daily activities (14%), affecting the quality of life. Dysmenorrhea can be overcome by non-pharmacological therapy, one of which is Effleurage massage. Purpose: The purpose of this research was to determine the effectiveness of Effleurage massage in decreasing dysmenorrhea in female students of Mojokerto district Junior High School, East Java. Methods: This research used quasi-experimental design with one group pretest-posttest with total sample of 25 respondents. The sampling method used nonprobability sampling technique; purposive sampling. Data was collected using a demographic data questionnaire and numeric rating scale (NRS) pain scale sheet. Results: Based on the statistical test, the Wilcoxon signed-rank test showed a value of p = 0.000, which means a difference in pain intensity before and after effleurage massage. Conclusion: Effleurage massage is effective in reducing dysmenorrhea. The success of giving Effleurage massage in dysmenorrhea turned out to increased blood circulation and sensory nerves to prevent pain transmission. This massage also releases endorphins and enkephalins that can reduce pain, increase comfort, relaxation, relax muscles, and reduce anxiety in patients. Endorphin compounds will be released by the body as a natural pain reliever and create a feeling of comfort